Resolution of Pseudophakic Cystoid Macular Edema: 2 mg Intravitreal Triamcinolone Acetonide versus 40 mg Posterior Sub-Tenon Triamcinolone Acetonide. (3rd June 2021) - Kuley, Brandon; Storey, Philip P.; Wibbelsman, Turner D.; Pancholy, Maitri; Zhang, Qiang (Ed); Sharpe, James; Bello, Nicholas; Obeid, Anthony; Regillo, Carl; Kaiser, Richard S.; Chiang, Allen; Fineman, Mitchell S.; et al.
ABSTRACT: Purpose: To compare 2 mg intravitreal triamcinolone (IVT) versus 40 mg posterior sub-Tenon triamcinolone acetonide (STT) for the treatment of eyes with pseudophakic cystoid macular edema. Methods: A retrospective, single-center review of eyes receiving 2 mg IVT between 3/1/2012-3/1/2017 and 40 mg STT between 1/1/2015-3/1/2017. Visual acuity (VA) and central macular thickness (CMT) were recorded at baseline, 1-, 3-, and 6-month follow-up visits. Results: Forty-five eyes were included in the IVT group and 50 eyes in the STT group. Change in VA from baseline to 1, 3, and 6 months was not significantly different between IVT and STT (6 months: 2.3 lines vs. 2.4 lines, p = .10). The IVT group achieved significantly better CMT improvement from baseline compared to STT at 1 month (255 μm vs. 187 μm; p = .03), but this difference was not present at month 3 (214 μm vs. 212 μm; p = .79) or month 6 (176 μm vs. 207 μm; p = .29). During the 6-month follow-up period, approximately 7% of eyes in the IVT group and 12% of eyes in the STT group developed ocular hypertension ( p = .43), and all cases were successfully managed with topical anti-ocular hypertensive therapy or observation. Conclusions: 2 mg IVT and 40 mg STT both achieved significant improvement in vision and CMT with no significant difference between interventions at 3- and 6-month follow-up.